2016
DOI: 10.1139/apnm-2015-0617
|View full text |Cite
|
Sign up to set email alerts
|

Examination of food industry progress in reducing the sodium content of packaged foods in Canada: 2010 to 2013

Abstract: Abstract:In 2010, as part of a national sodium reduction strategy, Canada published sodium reduction benchmark targets for packaged foods; however, no evaluation of this policy has occurred. The objective was to evaluate changes in the sodium content of packaged foods, identify categories reduced in sodium, and determine the proportion meeting Health Canada's sodium reduction benchmarks. This was a cross-sectional analysis of Canadian packaged foods in 2010 and 2013 (n = 10 487 and n = 15 394, respectively). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Risk of bias assessments for the four studies are included in Appendix S1. The studies were conducted in Australia, 8 Canada, 9 Spain 10 (high-income countries), and Iran 11 (an upper middle-income country); none were conducted in low-or lower middle-income countries. Two studies measured the effects of a multicomponent intervention (ie, advocacy, community mobilization, awareness campaigns, and salt substitution in Australia, and awareness campaigns and food reformulation in Iran)…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias assessments for the four studies are included in Appendix S1. The studies were conducted in Australia, 8 Canada, 9 Spain 10 (high-income countries), and Iran 11 (an upper middle-income country); none were conducted in low-or lower middle-income countries. Two studies measured the effects of a multicomponent intervention (ie, advocacy, community mobilization, awareness campaigns, and salt substitution in Australia, and awareness campaigns and food reformulation in Iran)…”
Section: Resultsmentioning
confidence: 99%
“…In relation to the NSRI, by 2014, data from US packaged foods showed that 43% of food categories had significantly reduced sodium, but most categories did not meet 2014 NSRI targets, and US dietary data suggest that sodium intake has not substantially declined (2,20). With implementation of Health Canada benchmarks, significant sodium reductions were observed in w16% of processed food categories by 2013, and further data on sodium intake reduction are not available to our knowledge (21). A 2017 Cochrane review provided evidence to suggest that voluntary national food standards may have a greater potential to reduce sodium intake when they are part of a multicomponent strategy including monitoring (42).…”
Section: Discussionmentioning
confidence: 95%
“…Both standards were based on the sodium content of foods that are produced by major food manufacturers. Although declines occurred in the sodium content of some US and Canadian commercially processed foods after the publication of these standards, sodium standards were not met for all food categories, and the potential impact on the change in sodium intake has been unclear (2,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium claims were not significantly higher in 2013 compared to 2010 [24], despite huge efforts directed towards sodium reduction in Canada during this time [19]. For example, other research has shown that little sodium reduction progress overall has been achieved in the food supply during this period, although significant improvement has been achieved in some food categories [38]. One reason for the lack of low/reduced sodium claims could be that food manufacturers are using a step wise approach to reduce sodium in foods, as suggested by Health Canada's sodium guidance document [19]; therefore, reductions are maybe not sufficient to reach the threshold of at least 25%, for a food to be allowed to carry a lower sodium nutrient content claim [13].…”
Section: Discussionmentioning
confidence: 99%